Influence of Fermented-Moutai Distillers' Grain on Growth Performance, Meat Quality, and Blood Metabolites of Finishing Cattle - Cheng, Qiming; Xu, Duhan; Chen, Yulian; Zhu, Mingming; Fan, Xueyin; Li, Maoya; Tang, Xiaolong; Liao, Chaosheng; Li, Ping; Chen, Chao (Frontiers in Veterinary Science, 2022)
The present study evaluated the effect of dietary supplementation with fermented-Moutai distillers' grain (FMDG) on the growth performance, meat quality, amino acid composition and blood metabolites of finishing cattle. Thirty cattle (2 years old; 237.55 ± 10.72 kg) were randomly assigned to one of three dietary supplementations: 0% FMDG (control), 15% FMDG (R1) and 30% FMDG (R2) [dry matter (DM) basis]. After 60 days, the inclusion of FMDG had no significant (p > 0.05) effects on the growth performance indices (dry matter intake, average daily gain and feed efficiency), meat quality (cooking yield, shear force, L*, a*, and b* values) or bovine blood biochemical indicators (except albumin and immunoglobulin A). Cattle fed R1 had the lowest (p = 0.001) loin eye area. Supplementation with FMDG significantly (p < 0.05) increased the beef contents of various amino acids (except isoleucine and arginine) compared with the control diet. Specifically, R2 significantly increased (p < 0.05) the total amino acid, essential amino acid, non-essential amino acid and umami amino acid contents in beef, while the difference in bitter amino acid content between different treatments was not significant (p = 0.165). These results suggest that it is feasible to include FMDG at up to 30% DM without affecting the growth performance, meat quality or blood metabolites of finishing cattle.